The Impact Of Financing Product Scheme To Islamic Banking Financial Performance - Fadilla Muhammad Mahdi; Fitrian Aprilianto (Jurnal Ilmiah Ekonomi Islam, 2023)
The aim of this study is to determine how different financing plans affect a bank's ability to earn income and manage financing risk throughout the course of both the short- and long-terms. The study utilizes an associative research design and a quantitative methodology. The Financial Services Authority's monthly aggregate reports on Islamic banking for the years 2012 to 2022 make up the study sample. Total debt-based financing, total profit-sharing financing, total leasing-based financing, return on assets (ROA), and non-performing finance (NPF) are among the variables included in the study model. Vector Error Correction Modelling (VECM), which enables the study of the data, is used to examine the short- and long-term effects of independent factors on the dependent variable. Two investigational models—the ROA model and the NPF model—are included in the study. According to the research's findings, when viewed from the NPF model's point of view, debt- and leasing-based financing are more secure over the long run for Islamic banks. Leasing-based financing, however, turns out to be more beneficial for Islamic banks from the standpoint of the ROA model